RLS-Based Control Algorithms for 3D Zones of Quiet - Małgorzata I. MICHALCZYK; Janusz SERWIN (Archives of Acoustics)
The paper summarises research on application of RLS-based (recursive least squares) adaptive control algorithms for single-channel active noise control (ANC) system, used to create three dimensional (3D) local zones of quiet in a reverberant enclosure by attenuation of tonal disturbances. Three different ANC system structures are concerned: classical “filtered-x”, modified “filtered-x” and “adjoint” structures. A problem of parameterisation of six RLS-based adaptive control algorithms is evaluated, initially in simulations with the use of nonsimplified plant models and tonal disturbances. Next, research results are proved in realworld experiments. Finally, the efficiency of ANC systems using different control structures and RLS-based control algorithms is compared.